2021
DOI: 10.1038/s41467-021-21712-4
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in BRAF disrupt the hypothalamo-pituitary axis leading to hypopituitarism in mice and humans

Abstract: Germline mutations in BRAF and other components of the MAPK pathway are associated with the congenital syndromes collectively known as RASopathies. Here, we report the association of Septo-Optic Dysplasia (SOD) including hypopituitarism and Cardio-Facio-Cutaneous (CFC) syndrome in patients harbouring mutations in BRAF. Phosphoproteomic analyses demonstrate that these genetic variants are gain-of-function mutations leading to activation of the MAPK pathway. Activation of the MAPK pathway by conditional expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Activation of the MAPK pathway by B-Raf V600E , or B-Raf Q241R , leads to abnormal cell lineage determination and terminal differentiation of hormone-producing cells, causing hypopituitarism. Expression of the B-Raf V600E in embryonic pituitary progenitors promotes expression of cell cycle inhibitors, cell growth arrest, and apoptosis, but not cancer ( 118 ). B-Raf V600E is also a common strong driver of cancer.…”
Section: Developmental Disorders May or May Not Involve The Same Mutations As Cancermentioning
confidence: 99%
“…Activation of the MAPK pathway by B-Raf V600E , or B-Raf Q241R , leads to abnormal cell lineage determination and terminal differentiation of hormone-producing cells, causing hypopituitarism. Expression of the B-Raf V600E in embryonic pituitary progenitors promotes expression of cell cycle inhibitors, cell growth arrest, and apoptosis, but not cancer ( 118 ). B-Raf V600E is also a common strong driver of cancer.…”
Section: Developmental Disorders May or May Not Involve The Same Mutations As Cancermentioning
confidence: 99%
“…After transsphenoidal resection, tumor was washed with PBS (pH 7.4) and cells were dispersed using 2.5% Trypsin, Gibco, USA and mechanical dispersion procedure. Cell culture was performed in Dulbecco Modified Eagle Media (DMEM, Gibco, USA) containing fetal calf serum (FCS, Gibco, USA), penicillin and streptomycin at 37 °C and 5% CO2.For immunofluorescence cells, were incubated with primary antibodies [anti-phospho β-catenin Ser552 (# 9566) (1:300), and anti-CD44 (ab157107) (1:100)] as described in [ 28 , 29 ]. After washing, cells were incubated with fluorochrome conjugated secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade, with increasing knowledge of molecular biological mechanisms, we have gathered more insight into the possible mechanisms underlying disturbances in growth hormone secretion, growth hormone resistance and growth plate disturbances. It has been shown that hypothalamic–pituitary genes of the RAS-MAP kinase pathway are involved in the development of the hypothalamic–pituitary axis [ 21 ], which suggests that the hypothalamic–pituitary architecture could be deranged in RASopathies. The previously reported neurosecretory deficiency could be explained by these changes in hypothalamic–pituitary morphology.…”
Section: Endocrine Featuresmentioning
confidence: 99%